The effectiveness of Cross-cultural training programmes - An empirical study on Italian Expatriates - Muggiani, Giulia (My University, 2015)
In todays’ globalized world, where business is international and expatriation is a widespread practice, cross-cultural training is still a current topic. Due to the controversy characterizing the extant literature, further insights of the topic are needed. Despite many scholars have studied CCT in fact, effectiveness literature presents a lack of a unitary and consistent perspective. Contradictory results instil in MNCs and practitioners a sceptical attitude, thus likely impeding the development and implementation of effective training programmes due both to the doubts surrounding the effectiveness of CCT and the unawareness of what makes a training programme effective. The purpose of this thesis is to gain a deeper understanding of the impact CCT programmes have on expatriates’ experience, specifically in terms of cross-cultural adjustment. Hence, Italian expatriates’ perspective was considered in order both to understand expatriates’ CCT experience and to provide new insights about the effects of CCT on CCA. The theoretical part of the study is based on CCT features and the existing CCT effectiveness literature, including the main theories guiding CCT research and development, and the relationship between CCT and CCA. The research design applied implies the qualitative research method. For this exploratory study, the empirical data were collected through non-standardized semi-structured interviews, and five Italian expatriates were interviewed. The empirical data were analysed and discussed related to the main theories examined in the literature review. The findings emerged reflected the expatriates’ perception of CCT and the evaluation of its effectiveness. The study showed that CCT was effective in enhancing adjustment through the development of realistic expectations, the improvement of work abilities and the enhancement of interaction with locals. It also appeared that the effect of CCT on CCA could be improved through the higher involvement of host nationals, the provision of in-country support and the combination of didactical and experimental training method. Further research is needed to understand the moderating effects factors as prior international experience and perceived training need may have on CCT outcome.
Keywords: Cross-cultural training; Cross-cultural adjustment; Expatriates; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|